Impact of Viral Marketing on Marketplace Purchase Decisions in Indonesia - Pratiwi, Dwi Indah; Noviarita, Heni; Anggraeni, Erike (Perpustakaan dan Penerbitan Unismuh Makassar, 2022)
This study aims to further examine the impact of the influence of viral marketing on purchasing decisions in the market place in Indonesia. The sample of this study used the slovin technique with a sample of 400 in the millennial generation in Indonesia. In this study, the resulting data was processed using the SPSS version 24 statistical tool with the Individual Parametric test (T test) on the basis of a significance level of 5%. The results of the study show that there is an impact of the influence of viral marketing on purchasing decisions in the market place in Indonesia. This happens because individuals as consumers in making purchasing decisions are obtained and influenced by the knowledge and clarity of the viral marketing content of the products that are created. In addition, with current digitalization very quickly, product content becomes viral, it can make an individual tend to be interested and curious about endemic product trends so that consumers are interested in buying products and thus serve as the basis for making decisions in purchasing in the Indonesian market place. The main and most important factor very important in the development of information through viral marketing is that it will increase trust for customers in making purchasing decisions in the market place.